Paediatric postdischarge mortality in developing countries: a systematic review - Nemetchek, Brooklyn; English, Lacey; Kissoon, Niranjan; Ansermino, John Mark; Moschovis, Peter P; Kabakyenga, Jerome; Kerry, Susan Fowler; Kumbakumba, Elias; Wiens, Matthew O (BMJ Open, 2018)
Objectives: To update the current evidence base on paediatric postdischarge mortality (PDM) in developing countries. Secondary objectives included an evaluation of risk factors, timing and location of PDM. Design: Systematic literature review without meta-analysis. Data sources: Searches of Medline and EMBASE were conducted from October 2012 to July 2017. Eligibility criteria: Studies were included if they were conducted in developing countries and examined paediatric PDM. 1238 articles were screened, yielding 11 eligible studies. These were added to 13 studies identified in a previous systematic review including studies prior to October 2012. In total, 24 studies were included for analysis. Data extraction and synthesis: Two independent reviewers extracted and synthesised data using Microsoft Excel. Results: Studies were conducted mostly within African countries (19 of 24) and looked at all admissions or specific subsets of admissions. The primary subpopulations included malnutrition, respiratory infections, diarrhoeal diseases, malaria and anaemia. The anaemia and malaria subpopulations had the lowest PDM rates (typically 1%–2%), while those with malnutrition and respiratory infections had the highest (typically 3%–20%). Although there was significant heterogeneity between study populations and follow-up periods, studies consistently found rates of PDM to be similar, or to exceed, in-hospital mortality. Furthermore, over two-thirds of deaths after discharge occurred at home. Highly significant risk factors for PDM across all infectious admissions included HIV status, young age, pneumonia, malnutrition, anthropometric variables, hypoxia, anaemia, leaving hospital against medical advice and previous hospitalisations. Conclusions: Postdischarge mortality rates are often as high as in-hospital mortality, yet remain largely unaddressed. Most children who die following discharge do so at home, suggesting that interventions applied prior to discharge are ideal to addressing this neglected cause of mortality. The development, therefore, of evidence-based, risk-guided, interventions must be a focus to achieve the sustainable development goals.
Keywords: Paediatric postdischarge mortality; Evaluation of risk factors; Timing and location of PDM